The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.18632/oncotarget.13723
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cancer antioxidant defense by natural compounds

Abstract: All classic, non-surgical anticancer approaches like chemotherapy, radiotherapy or photodynamic therapy kill cancer cells by inducing severe oxidative stress. Even tough chemo- and radiotherapy are still a gold standard in cancer treatment, the identification of non-toxic compounds that enhance their selectivity, would allow for lowering their doses, reduce side effects and risk of second cancers. Many natural products have the ability to sensitize cancer cells to oxidative stress induced by chemo- and radioth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
112
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(123 citation statements)
references
References 173 publications
(130 reference statements)
2
112
0
1
Order By: Relevance
“…Against, cancer cells boost their anti-apoptotic mechanisms like a nuclear factor kappa-light-chain-enhancer of activated B cell (NFĸB) pathway to escape cell death [9]. Disruption of redox balance in cells causes activation of the transcription factors like nuclear factor erythroid 2-related factor 2 (Nrf2), NFĸB, and activator protein 1 (AP-1) as redox-sensitive transcription factors [28]. Nrf2 transcription factor is the major driver of antioxidant expression that leads to protection against DNA damage, endogenous and exogenous hazards, and consequent cancer initiation [29,30].…”
Section: Relation Between Ros Actions With Promoting and Fighting Cancermentioning
confidence: 99%
“…Against, cancer cells boost their anti-apoptotic mechanisms like a nuclear factor kappa-light-chain-enhancer of activated B cell (NFĸB) pathway to escape cell death [9]. Disruption of redox balance in cells causes activation of the transcription factors like nuclear factor erythroid 2-related factor 2 (Nrf2), NFĸB, and activator protein 1 (AP-1) as redox-sensitive transcription factors [28]. Nrf2 transcription factor is the major driver of antioxidant expression that leads to protection against DNA damage, endogenous and exogenous hazards, and consequent cancer initiation [29,30].…”
Section: Relation Between Ros Actions With Promoting and Fighting Cancermentioning
confidence: 99%
“…Curcumin, a well‐known constituent of turmeric, is being evaluated for its effectiveness against several cancers including brain cancer, breast cancer, lung cancer, and prostate cancer (Ravindran, Prasad, & Aggarwal, ). Several polyphenols have shown potent anticancer effect because of their antioxidant property (Banerjee & Mandal, ; Sznarkowska et al, ). Overall, natural compounds have superior efficacy and more importantly lesser toxicity when compared with synthetic chemotherapeutic agents (Sak, ; Yuan, Ma, Ye, & Piao, ).…”
Section: Natural Products In Anticancer Therapy: Benefits and Challengesmentioning
confidence: 99%
“…Researchers also explored microbes and the marine organism as a source of natural compounds (Discovery, ). Nature‐derived compounds have various pharmacological activities including antiangiogenic (Sulaiman, Basavarajappa, & Corson, ), antiprotozoal (Jones, Grkovic, Sykes, & Avery, ; Singh, Mishra, Bajpai, Singh, & Tiwari, ), antiatherosclerotic (Orekhov, Sobenin, Revin, & Bobryshev, ), antimicrobial (Farha & Brown, ; Genilloud, ), anti‐obesity (Fu, Jiang, Guo, & Su, ), antioxidant (Fiedor & Burda, ), antidiabetic (Nazaruk & Borzym‐Kluczyk, ), hepatoprotective (Madrigal‐Santillán, ), anti‐inflammatory (Arulselvan et al, ), neuroprotective (Ebrahimi & Schluesener, ; Essa et al, ), and chemotherapeutic (Amin et al, ; Sznarkowska, Kostecka, Meller, & Bielawski, ; Yang et al, ) effects.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that tocotrienols were able to induce apoptosis in malignant cells, but not in non-malignant cells [8,9]. This selectivity could be largely due to the reduced antioxidant defense expressed by these malignant cells when compared to non-malignant cells [10] or might involve many other unknown factors. The selectivity of T3 for cancer cells might be dependent on the ability of the former to specifically target and downregulate proteins, which are abnormally upregulated in carcinogenic but not in normal cells.…”
Section: Introductionmentioning
confidence: 99%